Kinetic control of molecular assembly on surfaces. Issue 1 (December 2018) - Paris, Chiara; Floris, Andrea; Aeschlimann, Simon; Neff, Julia; Kling, Felix; Kühnle, Angelika; Kantorovich, Lev
Abstract It is usually assumed that molecules deposited on surfaces assume the most thermodynamically stable structure. Here we show, by considering a model system of dihydroxybenzoic acid molecules on the (10.4) surface of calcite, that metastable molecular architectures may also be accessed by choosing a suitable initial state of the molecules which defines the observed transformation path. Moreover, we demonstrate that the latter is entirely controlled by kinetics rather than thermodynamics. We argue that molecules are deposited as dimers that undergo, upon increase of temperature, a series of structural transitions from clusters to ordered striped and then dense networks, and finally to a disordered structure. Combining high-resolution dynamic atomic force microscopy experiments and density-functional theory calculations, we provide a comprehensive analysis of the fundamental principles driving this sequence of transitions. Our study may open new avenues based on kinetic control as a promising strategy for achieving tailored molecular architectures on surfaces. Kinetic control of self-assembly at interfaces offers a promising route to new two dimensional materials. Here high-resolution dynamic atomic force microscopy experiments combined with DFT calculations reveal the kinetic pathways by which 2, 5-dihydroxybenzoic acid sequentially assembles on calcite.